SP4.2.1 The Global impact of COVID-19 on Surgeons and Team members (GlobalCOST) Study. (28th October 2021) - Jaffry, Zahra; Sobti, Anshul; Negida, Ahmed; Singh, Bijayendra; Brennan, Peter; Imam, Mohamed
Abstract: Aims: To describe the impact of the COVID-19 pandemic on the well-being of surgeons and allied health professionals across the world and assess the support provided by their institutions. Methods: An online survey was distributed through medical organisations, social media platforms and collaborators from the 15 th of July to the 15 th of December 2020. Results: 1590 responses were received. 80.0% were surgeons, 6.4% nurses, 5.3% assistants, 3.1% anaesthetists, 1.4% operating department practitioners and 3.8% classed as other. Of participants, 64.0% had found difficulty gaining access to personal protective equipment (PPE), 29.8% had not received training on its use and 32.0% had become physically ill since the start of the pandemic (59.9% of which were due to COVID-19 symptoms). 29.0% saw a decrease in salary and 35.2% a decrease in time spent with family. Between a time two weeks before the start of the pandemic and after, there was a significant increase in mean scores for depression (4.22 (CI = 3.98-4.46)) and anxiety (2.24 (CI = 2.01-2.46)), based on the Patient Health Questionnaire (PHQ-9) and Generalised Anxiety Disorder Assessment (GAD-7) respectively (p < 0.0001). In terms of support, only 36.0% had easy access to occupational health, 58.5% were able to take regular breaks, 16.5% had access to 24 hour rest facilities and 14.2% to 24 hour food and drink facilities. Conclusions: This work has highlighted a need and ways in which to improve conditions for the health workforce. This will inevitably have a positive effect on the care received by patients.